BOARD QUALITIES AND EARNINGS MANAGEMENT: THE INTERMEDIARY ROLE OF COMPANY SIZE (World Economics and Finance Bulletin, 2024)
This paper aims to uncover board qualities, namely size, meetings, autonomy, gender diversity, and administrative ownership. Thus, it also investigates how far these qualities can affect the practices used in earnings management. To this end, the paper focuses on the companies which are involved in four different business sectors and that are listed on Iraq's stock exchange. Therefore, this paper questions how far the determination of board qualities can help reduce the opportunistic practices used to fix earnings. The sample is 35 non-financial share-holding companies listed on Iraq's stock exchange from 2010 to 2021. Additionally, 420 views per study variable were conducted to verify the hypotheses, focusing on the correlation between board qualities and earnings management with the company size as an intermediary role. Concerning study variables, earnings management was considered a dependent variable, board qualities an independent variable, and the company size an intermediate variable. Furthermore, the control variables, represented by the company performance and the company history, were also added to the variables. This study finds that board qualities, considering how big some boards are, had no effect on earnings management. Also, the size of the boards in these companies neither reduces executive managers' opportunistic practices nor does it cut earnings managements. Moreover, board qualities do impact earnings management by as many board meetings as possible. Finally, the paper proposes several recommendations. It is highly necessary that the Iraqi stock exchanges urge companies listed thereon to appoint independent, skilled, and financially experienced members to boards, provided they hold no executive and independence-curbing positions. Legislations to regulate earnings management must be enacted. Finally, companies are urged to use experts from large audit firms on account of their physical, financial, and technical potentials
Keywords: Corporate boards; Earnings managements; Company potentials